Preoperative growth inhibition of human gastric adenocarcinoma treated with a combination of celecoxib and octreotide - Huang Mao-tao; Chen Zhi-xin; Wei Bing; Zhang Bo; Wang Chun-hui; Huang Ming-hui; Liu Rui; Tang Cheng-wei (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: To gain insight into the histopathological responses and molecular targets in the inhibition of growth of human gastric cancer treated with celecoxib (a cyclooxygenase [COX]-2 inhibitor) combined with octreotide. Methods: Seventy five patients with gastric cancer undergoing curative gastrectomy or extended resection were randomly divided into 3 groups. The apoptosis of tumor cells was measured by terminal deoxynucleotide transferase-mediated dUTP nick end-labeling (TUNEL) assay. Gastric cancer microvessel density (MVD) and the expression of COX-2 were evaluated by immunohistochemical staining. The expression of somatostatin receptor (SSTR)-2 was detected with the biomolecular interaction analysis system. The transcription of non-steroidal anti-inflammatory drug-activated gene (NAG)-1 was measured by RT-PCR. Results: Compared with the control and celecoxib groups, more necrosis in the combination group was observed. The apoptotic rate in the combination group (7.06%±0.67%) was significantly higher than that in the control group (6.23%±1.29%, P